Navigating a Climate in Crisis through a Biomimetic Epistemology: Rethinking Design Education in the Anthropocene - McCormick, Elizabeth; Thaddeus, David (Enquiry The ARCC Journal for Architectural Research, 2024)
We have entered a geological epoch where environmental change is driven primarily by human activity. The technology-centric approach to sustainable development as the dominant model of innovation in industrialized countries has led to expansive ecological degradation. This paper critiques this paradigm and builds on existing literature from environmental philosophy to propose a new model of ethical, bio-inspired architectural thinking. Though Biomimicry is often celebrated as a model for nature-inspired innovation, it can inadvertently reinforce notions of mastery over nature, a harmful phenomenon that environmental philosopher Freya Mathews calls ‘anthropocentric triumphalism.’ In response to those challenges, this paper explores the philosophical underpinnings of bio-inspired design to advocate for a transformative pedagogical model within architectural education and practice. By exploring the conflicts implicit in biomimetic processes, we aim to disentangle students’ thinking from techno-centric models and prepare them for the broader societal implications of a necessary energy shift. This exploration emphasizes the importance of cultivating a holistic understanding of ecological systems, urging designers to appreciate the intricate relationships within ecosystems rather than viewing them solely as sources of technological inspiration. By addressing the conflicts inherent in biomimetic processes, this paper calls for a more comprehensive and ethical approach to biomimicry – one that emphasizes both the source of knowledge as well as its application. Ultimately, we seek to foster a responsible relationship between architecture and the natural world, paving the way for a sustainable future that goes beyond mere imitation to encompass true coexistence.